I-CARE: A Scaffolded Instructional Approach to Teach Teachers and Staff Self-Care Practices within Juvenile Justice Facilities - Sanders, Sara; Kumm, Skip; Ansley, Brandis M.; Jolivette, Kristine (Journal of the American Academy of Special Education Professionals, 2022)
Staff who work in juvenile justice settings frequently face high levels of occupational stress, secondary trauma, and burnout as a result of numerous stressors. Without recourse, these stressors can negatively impact staff well-being, and decrease staff self-efficacy and ability to implement treatment programming to the youth they serve with fidelity. One way to reduce staff levels of occupational stress and improve well-being is consistent use of self-care practices. It is critical to develop an effective approach to support the increase of self-care practices among staff in juvenile justice facilities. The I-CARE instructional approach, influenced by the self-regulated strategy development (SRSD) and multi-tiered system of support (MTSS) frameworks, is one such method for teaching daily self-care practices. We describe the I-CARE instructional approach and how it can be supported within juvenile justice facilities.